Pengaruh Kemampuan Manajerial dan Supervisi Akademik Kepala Sekolah terhadap Kinerja Guru Sekolah Dasar di Gugus Lampeuneurut Aceh Besar - Budiati, Kartiningsing; Musdiani, Musdiani; Putra, Mulia; Sari, Siti Mayang (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine whether there is an influence of the principal's managerial ability and academic supervision on teacher performance in Aceh Besar. This research uses a quantitative approach with ex post facto research type. Data collection was carried out using closed questionnaires. Data analysis was performed quantitatively using multiple linear regression analysis. The results proved that there was an influence on the principal's managerial ability on teacher performance. There is an influence of the principal's academic supervision on teacher performance, there is an influence between managerial ability, academic supervision of the principal on the performance of elementary school teachers in the Lampeuneurut Cluster